The Sociology of Reading Among Malaysian Youths: Building A Culture of Reading to Enhance Environmental Awareness and Develop Pro-Environmental Behavior - Rasiah, R.; Kaur, H.; A.H., Baharom; Turner, J.J.; Habibullah, M.S.; Dayang Affizzah, Awang Marikan (JESTP, 2022)
Malaysia established its Eleventh Malaysia Plan (11MP) to achieve sustainable economic development, with one of its primary strategic thrusts being "accelerating human capital development for an advanced nation." This study examines one aspect of human capital development by reviewing the reading habits of Malaysian youths and the conjecture surrounding a 'crisis' among youths and their engagement with reading, to foster a culture of reading to improve education, focusing on human behavioral interventions to increase environmental knowledge and awareness, and developing human capital with pro-environmental behavior. Data from 250 valid questionnaires was analyzed using the variance-based Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The theoretical framework of this study is based on Dewey's Educational Theory of Constructivism and Social Cognitive Theory. The results reveal that attitude and parental influence significantly promotes reading habits, while perceived stress does not. It was also found that reading habits positively influenced the pro-environmental behavior of youths. It is hoped that this study will lead to a coherent strategy being undertaken to engage Malaysian youths not only to read but to engender a culture of sustainability and pro-environment behavior.